Evaluation of bulk density and vegetation as affected by military vehicle traffic at Fort Riley, Kansas - Retta, Amare; Wagner, Larry E.; Tatarko, John; Todd, Timothy C. (My University, 2013)
Studies were conducted using military vehicles to determine the influence of repeated traffic on soil compaction and vegetative losses. The resultant data will eventually be incorporated into models such as the Wind Erosion Prediction System (WEPS). A replicated field experiment was conducted in the fall of 2010 on two soils that dominate the military training grounds at Fort Riley, Kansas. Treatments consisted of two vehicle types and three levels of vehicle passes. We used an Abrams M1A1 tank and a High-Mobility Multipurpose Wheeled Vehicle (i.e., Humvee), representing tracked and wheeled military vehicles, respectively. Bulk density, aboveground standing biomass, and plant cover were measured before and after vehicular traffic in the fall of 2010 as well as in the spring and summer of 2011. Samples were taken from curved, straight, and cross-over sections of the vehicle tracks. A mixed-model analysis of variance of these data indicated that the overall mean bulk density under the M1A1 was significantly greater than under the Humvee (p ≤ 0.05). In general, as the number of passes increased, the bulk density under the M1A1 increased significantly (p ≤ 0.05), but the increases under the Humvee were not significant (p ≤ 0.05). Bulk densities were significantly greater in the curved part of the tracks than the straight part of the tracks. Reduction in standing biomass and vegetation cover was more severe on average under the M1A1 than under the Humvee (although not significant at p ≤ 0.05). For both vehicles, biomass and cover were affected more at the curved sections of the track than the straight sections (significant at p ≤ 0.05). Comparison of spring and fall bulk density data showed significant differences at the 0-5 cm and 5-10 cm depths, indicating that the winter freeze and thaw cycles loosened the top soil layers. Subsequent growth showed severe reduction in grass biomass growth in the curved sections of the tracked vehicle paths. Growth in forb species was not significantly affected.
Citation: Retta, A., Wagner, L., Takarto, J., Todd, T. (2013). Evaluation of bulk density and vegetation as affected by military vehicle traffic at Fort Riley, Kansas. Transactions of the ASABE, 56(2), 653-665. https://doi.org/10.13031/2013.42687
Keywords: Forb biomass; Grass biomass; Humvee; M1A1; Military training; Wind erosion